Dynamics of Capital Flight Components and Domestic Investment in Nigeria - Ahmed Oluwatobi Adekunle (Fakultas Ekonomi, Universitas Bangka Belitung, 2023)
This study examines the interconnection between the capital flight components and domestic investment in Nigeria. We employ Autoregressive Distributive Lag model to analyse the data for Nigeria spanning from1986 to 2020. The results show that changes in external debt, current account balance, and foreign direct investments have a negative effect on domestic investments in the short run and long run. The external reserve component shows a positive and significant effect on the domestic investment. The error correction coefficient is significant and conforms to a priori expectation. We conclude that growth in domestic investment can be achieved by regulating the component of capital flight within the desirable limit needed to stimulate growth in domestic investment.